Garcinia exigua (Clusiaceae), a new record for Thailand - Ngernsaengsaruay, Chatchai; Boonthasak, Weereesa; Meeprom, Nattanon; Tetsana, Naiyana; Suddee, Somran (Thai Forest Bulletin (Botany), 2023)
Garcinia exigua (Clusiaceae), previously known from Borneo [Malaysia (Sarawak) and Brunei], is reported as a new record from dry evergreen forest on limestone hill in Krabi Province, Peninsular Thailand. A detailed morphological description, illustrations and a distribution map of the species are provided, along with information on distribution, specimens examined, habitat, conservation status, phenology, etymology and vernacular name.